Assessing climate change impacts on coastal infrastructure in the Eastern Caribbean - Lewsey, Clement (2004)
Addresses current trends in land-use planning and, in the context of climate change, in particular sea-level rise, their impact on the coastal ecosystems of the Eastern Caribbean small islands. Makes recommendations that can help minimize the harmful impacts of these trends.